The Effectiveness of Virtual Work to Keep Achieving Optimal Performance Amid the Covid-19 Virus Outbreak - Wiradendi Wolor, Christian; Aminah, Hania; Rahmi; Martono, S. (International Journal of Criminology and Sociology, 2022)
Currently around the world affected by the covid-19 virus or known as the corona. Virtual work is now important to do besides the outbreak of this virus case. This is a challenge for the company and employees in facing the coronavirus epidemic. The purpose of this study is to find out and explain the effectiveness of virtual working to achieve optimal employee performance amid the covid-19 pandemic. This research is a systematic review (Systematic Review) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) method which is carried out systematically by following the correct stages or research protocols. Next, we present the results of our analysis in the form of recommendations in the implementation of virtual work activities. we recommend six approaches to support virtual work, namely the first is managerial support, the second is infrastructure, the third is a new policy and new rules, the fourth is scheduling, the fifth is trust, communication, and feedback, the sixth is technology applications, the last is knowledge sharing.